A Contingent Model for Evaluating Enterprise Systems' Benefits Using Competing Value Approach - Teo, Leon Kok Yang; Singh, Mohini; Cooper, Vanessa (ACIS, 2014)
Enterprise Systems (ES) are complex IT systems adopted by organisations to support business and increased productivity and efficiencies from integration, automation and reengineering of processes, as well as management of large volumes of data. Although investment in ES implementations is large, not all organisations achieve the benefits anticipated from ES implementations. A critical review of literature suggests that contingency factors such as organisational learning and innovation have an impact on ES benefits achieved. The conceptual framework proposed in this paper extends an exploratory study on the impact of organisational learning and innovation on ES benefits realisation using the Competing Value Theory for evaluating ES benefits.